High usability of a smartphone application for reporting symptoms in adults with cystic fibrosis - Wood, Jamie; Jenkins, Susan; Putrino, D.; Mulrennan, S.; Morey, S.; Cecins, N.; Hill, Kylie (Royal Society of Medicine Press, 2017)
© 2017, The Author(s) 2017. Introduction: In cystic fibrosis, exacerbations impair lung function and health-related quality of life, increase healthcare costs and reduce survival. Delayed reporting of worsening symptoms can result in more severe exacerbations and worse clinical outcomes; therefore there is a need for a novel approach to facilitate the early identification and treatment of exacerbations in this population. This study investigated the usability of a smartphone application to report symptoms in adults with cystic fibrosis, and the observer agreement in clinical decision-making between senior clinicians interpreting smartphone application responses. Methods: Adults with cystic fibrosis used the smartphone application weekly for four weeks. The application comprised 10 yes/no questions regarding respiratory symptoms and two regarding emotional well-being. Usability was measured with the System Usability Scale; Observer agreement was tested by providing a cystic fibrosis physician and a nurse practitioner with 45 clinical scenarios. For each scenario the clinicians, who were blinded to each other's responses, were asked to indicate whether or not they would: (i) initiate telephone contact, and/or (ii) request a clinic visit for the individual. Results: Ten participants (five female), aged mean (SD) 33 (11) years, FEV1 49 (27)% predicted completed the study. The mean (SD) System Usability Scale score was 94 (6). There was perfect agreement between clinicians for initiating contact with the participant (? = 1.0, p < 0.001), and near-perfect for requesting a clinic visit (? = 0.86, p < 0.001). Discussion: The use of a smartphone application for reporting symptoms in adults with cystic fibrosis has excellent usability and near-perfect agreement between senior clinicians when interpreting the application responses.